2006
DOI: 10.1002/acp.1301
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effects of misleading information on witness accuracy: can experts tell jurors something they don't already know?

Abstract: This study investigated potential differences between expert and lay knowledge of factors influencing witness suggestibility. Expert psychologists (N ¼ 58), jurors (N ¼ 157), and jury-eligible undergraduates (N ¼ 220) estimated the effects of misleading information on witness accuracy for three age groups in various conditions. Respondents possessed similar knowledge of age-related trends in suggestibility, the positive effects of a pre-misinformation warning, and the negative influence of longer delays betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 44 publications
2
41
1
Order By: Relevance
“…These findings comport with the body of work finding that prospective jurors understand that child witnesses are more suggestible than adults in the context of forensic interviews (e.g. McAuliff & Kovera, 2007;Quas, Thompson, & Clarke-Stewart, 2005).…”
Section: Confession Evidencesupporting
confidence: 86%
“…These findings comport with the body of work finding that prospective jurors understand that child witnesses are more suggestible than adults in the context of forensic interviews (e.g. McAuliff & Kovera, 2007;Quas, Thompson, & Clarke-Stewart, 2005).…”
Section: Confession Evidencesupporting
confidence: 86%
“…Previous research has consistently shown few differences between the responses of undergraduate college students and those of jury-eligible citizens (see Bornstein, 1999). Of importance, for the purposes of this study, Quas et al (2005) and McAuliff and Kovera (2007) found that beliefs or knowledge about child witnesses were rarely different for their college versus jury samples.…”
mentioning
confidence: 82%
“…A second shortcoming of most studies is the use of the all-inclusive term "children" (for exceptions, see McAuliff & Kovera, 2007;Quas et al, 2005). Developmental changes in memory and suggestibility are pervasive and dramatic (Ceci & Bruck, 1993, 1995, with preschoolers being most vulnerable to memory loss, distortion and suggestibility (although see Brainerd & Reyna, 2012).…”
mentioning
confidence: 98%
See 2 more Smart Citations